Development of ludical activity concearning the teaching and popularization of paleontology - Melo, Diogo Jorge de; Bastos, Ana Carolina Fortes; Rodrigues, Vanessa Maria da Costa; Monção, Vinícius de Moraes (Anuário do Instituto de Geociências, 2007)
Herein is described the development of a ludical activity in Paleontology with the purpose to apply the concepts of the geological time and the processes that occurred along the history of the Earth. This activity, that was teste in the event "Bio na Rua" of the Universidade Federal do Rio de Janeiro, consisted on the use of didactic panels concerning paleontological themes, geological time chart, fossil and ichnofossil concepts, the development of a board game showing the Earth history and origami workshops.